Comparative Transpiration Rates of Six Eucalyptus Species - Kaul, O. N.; Negi, J. D. S. (Indian Forester, 1979)
Comparative transpiration rates of siz Eucalyptus species viz. E. teretlicornis, E. hybrid, E. paniculata, E. robusta, E. albrz and E. saligna, under adequate moisture and stress conditions were studied along with their water deficit percentages. The results show that E. tereticornis, and E hybrid not only have lower rates of transpiration both under adequate moisture and stress conditions, but also possess inherent tissue characteristics to maintain higher level of hydration even under stress conditions. It is concluded that these two species tnay be more drought tolerant as compared to other species investigated.